Deriving meaning from others’ emotions: attribution, appraisal, and the use of emotions as social information - van Doorn, Evert A.; van Kleef, Gerben A.; van der Pligt, Joop (Frontiers in Psychology, 2015)
Emotional expressions constitute a rich source of information. Integrating theorizing on attribution, appraisal processes, and the use of emotions as social information, we examined how emotional expressions influence attributions of agency and responsibility under conditions of ambiguity. Three vignette studies involving different scenarios indicate that participants used information about others' emotional expressions to make sense of ambiguous social situations. Expressions of regret fueled inferences that the expresser was responsible for an adverse situation, whereas expressions of anger fueled inferences that someone else was responsible. Also, expressions of anger were interpreted as a sign of injustice, and expressions of disappointment increased prosocial intentions ( i.e.: to help the expresser. The results show that emotional expressions can help people understand ambiguous social situations by informing attributions that correspond with each emotion’s associated appraisal structures. The findings advance understanding of the ways in which emotional expressions help individuals understand and coordinate social life.